Aplicación de estrategias ergonómicas para el control de trastornos musculoesqueléticos en el personal de auxiliares de enfermería en Medicina Interna del Hospital General docente Riobamba. - Barragán Guevara, Karen Victoria (2017)
The objective of this research was to apply ergonomic strategies for the prevention of musculoskeletal disorders, when ergonomic risks were detected in the tasks of manual manipulation of patients, carried out by the staff of nursing assistants of the Internal Medicine service of the Riobamba General Teaching Hospital. The study population consisted of 15 nursing assistants, 13 women and 2 men, excluding a nursing assistant who had a chronic underlying disease. Initially, the Kuorinka Nordic questionnaire was applied to detect and analyze musculoskeletal symptoms. Subsequently, the relevant clinical assessment was made to determine these lesions. Once the initial phase was completed, ergonomic strategies were applied through the training of health personnel, considering topics such as the adequate mobilization of patients and the application of active pauses to avoid the appearance of symptoms due to musculoskeletal disorders. Finally, an ergonomic re-evaluation was carried out by means of the application of the Nordic questionnaire and clinical re-evaluation after 11 months, by means of the statistical analysis of the data, it was evidenced that the application of ergonomic measures were significant since the symptomatology for musculoskeletal disorders decreased in recurrence as well as in intensity, it was also concluded that the disorders located in the dorsal lumbar region were the most frequent in the personnel of nursing auxiliaries of the Internal Medicine Service. It should be noted that the average age is 50 years and that the female sex corresponds to 87% of the total population